Serial extraction: Variables associated to the extraction of premolars - Lara, Tulio Silva [UNESP]; dos Santos, Cibelle Cristina Oliveira; da Silva Filho, Omar Gabriel; Garib, Daniela Gamba; Bertoz, Francisco Antônio [UNESP] (My University, 2011)
Objective: To determine the frequency of patients who require extraction of permanent premolars among those treated with extraction of deciduous teeth for the correction of incisor crowding in the mixed dentition and analyze possible associated variables. Methods: The sample was composed of orthodontic records of 70 patients with permanent dentition whose treatment had begun in the mixed dentition phase and involved serial extraction. All records were analyzed by a single examiner to determine whether serial extraction had been performed with extraction of permanent teeth or only deciduous teeth. Associations were investigated between extraction of permanent teeth and lateral facial pattern, sagittal relationship of the dental arches, incisor-mandibular plane angle, size proportion of mandibular second molar/retromolar space, mechanics for space control and tooth-arch size discrepancy (Fisher's exact test for categorical variables and logistic regression for numeric variables, p<0.05). Results: Among the patients who had been treated with extraction of deciduous teeth, 70% required the extraction of permanent teeth. The statistical analysis revealed no significant associations between the analyzed variables and the need for permanent tooth extraction, with the exception of tooth-arch size discrepancy. Conclusion: Tooth-arch size discrepancy was the main factor determining premolar extraction in a serial extraction program.
Keywords: Malocclusion. mixed dentition. serial extraction